Designing Compact Products for Communal Spaces to Support Communal Activities - Salsabila Ayunda; Gabriella Chrismaditya Putri Mawarni; Afdhel Haqiqie Zahidin; Anisa Silviana Putri; Faisal Amien Prawira; Soewardikoen Soewardikoen (Publikasi Indonesia, 2024)
The city of Bandung is dubbed as a creative city as a result of a process carried out by local communities engaged in the creative industry. One of the areas that is used as a forum by creative people in the city of Bandung is Laswee creative space. Areas and spots in Laswee can be used by various communities on a regular basis for exhibitions, seminars, workshops, event design, and other gathering events. However, from the various facilities and environments that have been provided by Laswee as a creative communal space, there are still some aspects that have not been fulfilled for. Based on the emphatize and define process in this study, it shows that the furniture used in Laswee has not supported creative communal activities. Based on this, this research aims to produce compact furniture designs that are able to maximize communal and creative activities.